Lead absorption and renal dysfunction in a South African battery factory. Issue 7 (July 1998) - Ehrlich, R; Robins, T; Jordaan, E; Miller, S; Mbuli, S; Selby, P; Wynchank, S; Cantrell, A; De Broe, M; D'Haese, P; Todd, A; Landrigan, P
Abstract : OBJECTIVES: To test the association between inorganic lead (Pb) exposure, blood pressure, and renal function in South African battery factory workers, with both conventional and newer measures of renal function and integrity. METHODS: Renal function measures included serum creatinine, urea, and urate (n = 382). Urinary markers (n = 199) included urinary N-acetyl-beta-D-glucosaminidase (NAG), retinol binding protein, intestinal alkaline phosphatase, tissue non-specific alkaline phosphatase, Tamm-Horsfall glycoprotein, epidermal growth factor, and microalbuminuria. RESULTS: Mean current blood Pb was 53.5 micrograms/dl (range 23 to 110), median zinc protoporphyrin 10.9 micrograms/g haemoglobin (range 1.9 to 104), and mean exposure duration 11.6 years (range 0.5 to 44.5). Mean historical blood Pb, available on 246 workers, was 57.3 micrograms/dl (range 14 to 96.3). After adjustment for age, weight and height, positive exposure response relations were found between current blood Pb, historical blood Pb, zinc protoporphyrin (ZPP), and serum creatinine and urate. Blood pressure was not associated with Pb exposure. Among the urinary markers, only NAG showed a positive association with current and historical blood Pb. CONCLUSION: An exposure-response relation between Pb and renal dysfunction across the range from < 40 to > 70 micrograms/dl blood Pb was found in this workforce, with conventional measures of short and long term Pb exposure and of renal function. This could not be explained by an effect on blood pressure, which was not associated with Pb exposure. The findings probably reflect a higher cumulative renal burden of Pb absorption in this workforce in comparison with those in recent negative studies. The results also confirm the need for strategies to reduce Pb exposure among industrial workers in South Africa.